Validating the antecedents of the teacher commitment: A pilot study - Yang Shao; Sabariah Sharif; Connie Shin @ Connie Cassy Ompok (Human Resource Management Academic Research Society, 2025)
Teacher commitment is important for enhancing teaching quality, improving student learning outcomes and reducing teacher turnover, ensuring continuity and stability in education. However, external factors such as inadequate organizational support, excessive role pressure, or limited opportunities for personal growth can have a negative impact on teacher engagement, leading to burnout and decreased job satisfaction. Based on social exchange theory and social cognitive theory, this study constructed an analytical framework to explore the intrinsic mechanisms between teacher engagement and perceived organizational support, reward satisfaction, and self-efficacy. The study used a sample of 223 teachers from a university in Qingdao and collected data through an online survey with simple random sampling. The usability and reliability of the research instrument were rigorously validated through content validity index and pilot study. The scales used in this study demonstrated good reliability and validity, with Cronbach's alpha values exceeding 0.7 and KMO values above 0.6, supporting their internal consistency and suitability for factor analysis. Exploratory factor analysis confirmed the theoretical structures of the scales, retaining effective items with strong factor loadings to ensure accurate measurement of the respective constructs. The measurement tool developed in this study is well-designed to provide a reliable basis for broader academic research, and its applicability in different contexts was confirmed by rigorous pretesting, providing a methodological reference for future research in related fields.